POTENSI DAN PELUANG KELAYAKAN EKSPOR ARANG TEMPURUNG KELAPA (Coconut shell charcoal) DI KABUPATEN BANYUMAS - Maya Kartika Sari (MEDIAGRO, 2011)
Banyumas Regency is one of the regency in Central Java that produce coconut. Based on the data from Department of Forestry and Agriculture Banyumas Regency showed that the amount of coconut production in the last 2008 were 12,597.74 tons. It showed that Banyumas has  enough potential in developing the coconut commodity.  Recently, the waste of coconut in Banyumas Regency is not used effectively, for example coconut shell is only being used as charcoal for fish, satay and rubbering. Moreover, coconut shell still can be used as useful product, example Coconut Shell Charcoal. The objective of this research were explain the pattern and consistence of world market offer of coconut shell charcoal in Banyumas Regency, to analyze the feasibility export and the ability of entrepreneur to produce the of coconut shell charcoal in the village small industry in Banyumas Regency, and to find out the complete procedure in export matter.   Research method used was survey method. Research was conducted on March until April 2009. Data collection was conducted by using the primary data example interview, observation, and secondary data from Department of Forestry and Agriculture of Banyumas Regency, literature and internet business gallery Alibaba.com. Data analysis were using descriptive analysis, feasibility analysis of export as finansial, analysis of importir price offer and sensitivity analysis. The result of analysis showed that Banyumas Regency has potency to produce 120,000 kg Coconut shell charcoal every month.  That amoun showed Banyumas Regency could export around 5 containers and continuously. The demand trend happened in export opportunity of Coconut shell charcoal was fix demand, because during six months there was demand for the similar product in site business gallery Alibaba.com. Coconut shell charcoal in Banyumas Regency was feasible to be exported because the price from importer was US$200 per ton  (Rp2,200,00 per kg) it is still higher compared  with entire cost from Free on Board (FOB) and  higher from the price offered by exporter was Rp.2,000.00 per kg for 5 container delivery, so from the price of offering export was feasible to be followed up. The appropriate procedure of payment to conduct the international trade was by using the system of Letter of Credit (L/C). L/C that was requested by the exporter is L/C which has the certainty level of payment that was Irrevocable L/C because this L/C has certain agreement. Keywords : coconut shell corcoal, letter of credit, export, import.